Sustainability practices and lifestyle groups in a rapidly emerging economy: a case study of Chennai, India. (2016) - Tudor, Terry; Holt, Chris; Freestone, Nigel; Bhaskaran, G.; Suresh, M.; Banga, Sindy
The development of strategies to encourage more sustainable approaches to resource consumption is a key global challenge. This is particularly the case within rapidly developing countries such as India, due to rapid urbanisation, population growth and resource consumption. Using households in the Southeastern Indian city of Chennai as the case study, this study sought to examine the extent to which lifestyles could be categorised into groups and the role of the concepts of sustainability on these groups. Five lifestyle groups were identified, ranging from 'dedicated environmentalists', to non-environmentalist'. Conservation of electricity and water were key sustainability behaviours. Various key factors were found to impact upon the behaviours of individuals in these groups including perceived limitations in time, levels of awareness, as well as values. The implications of the findings for facilitating improved policies and practices are discussed.